Nilai-Nilai Budaya dalam Novel Batu Manikam Karya Bernard Batubara dan Implikasinya Terhadap Pembelajaran Bahasa Indonesia di SMA - Mery Nurfa Dilla; Afnita Afnita (Lembaga Pengembangan Kinerja Dosen, 2023)
The emergence of literary works is not solely written to provide entertainment to readers, but this is also a means of instilling cultural values ​​in the lives of readers. The presence of cultural values ​​in a literary work aims to provide positive values ​​in people's lives which will become a human guide in behaving. In addition, this cultural value will be a driving factor for a good way of thinking in society. This study aims to analyze cultural values ​​in one of Bernard Batubara's novels because the novel contains many life values, especially cultural values. This research is a type of library research. The data in this study is in the form of a novel entitled